h-Preinvex fuzzy processes - Matłoka, Marian (Silesian Statistical Reviev, 2016)
We introduce the notion of ℎ -preinvex fuzzy processes. We study their properties and give some inequalities of Hadamard-type for h-convex fuzzy processes
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2016, Nr 14 (20), s. 27-39
Keywords: h-preinvex fuzzy process; Hadamard’s inequalities